IT risk : turning business threats into competitive advantage - Westerman, George, 1963-; Hunter, Richard, 1952- (Boston, Mass. : Harvard Business School Press, 2007)
This book is a useful source of ideas, insights and examples for several different types of executives and managers from both business units and IT. it is based on extensive research from the Centre for Information Systems Research at MIT Sloan School of Management (MITCISR) and from Gartner Executive Programs.
Includes bibliographical references and index.
osc 04/06/13
Loans
Keywords: Information technology -- Management; Management information systems; Risk management; Information technology -- Security measures